The magic of computer graphics : landmarks in rendering - Kurachi, Noriko; Stark, Michael M. (CRC Press, 2011)
"Starting from the basic behavior of light, the first section of the book introduces the most useful techniques for global and local illumination using geometric descriptions of an environment. The second section goes on to describe image-based techniques that rely on captured data to do their magic. In the final section, the author looks at the synthesis of these two complementary approaches and what they mean for the future of computer graphics." -- Provided by publisher